2022
DOI: 10.1177/21582440221114333
|View full text |Cite
|
Sign up to set email alerts
|

The Factors of Continuance Intention to Use Mobile Payments in Sudan

Abstract: The advancement of technology in the field of telecommunications and increasing use of smartphones worldwide has simplified the purchasing and payment process via mobile devices. This new payment method enables people to enjoy services in a flexible and convenient manner while going about their daily activities. This study explores the continued use of mobile payment antecedents in Sudan. A total of 453 questionnaires were collected; SPSS and AMOS were used to test the proposed theoretical model using structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 102 publications
7
7
0
Order By: Relevance
“…According to the research findings, an individual's BI to use CLT is mainly determined by their PE of such transactions. This finding is in line with previous studies conducted in various contexts (Giovanis et al 2019 ; Madan and Yadav 2016 ; Sleiman et al 2022 ; Lu and Kosim 2022 ; Saha and Kiran 2022 ). It suggests that people are more inclined to adopt and utilize CLT if they believe that doing so will enhance their everyday experiences.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…According to the research findings, an individual's BI to use CLT is mainly determined by their PE of such transactions. This finding is in line with previous studies conducted in various contexts (Giovanis et al 2019 ; Madan and Yadav 2016 ; Sleiman et al 2022 ; Lu and Kosim 2022 ; Saha and Kiran 2022 ). It suggests that people are more inclined to adopt and utilize CLT if they believe that doing so will enhance their everyday experiences.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the study's outcomes suggested that the EE needed to complete CLT significantly affects users' BI to adopt CLT methods. These results are consistent with previous studies (Giovanis et al 2019 ; Teo et al 2015 ; Sleiman et al 2022 ; Lu and Kosim 2022 ; Saha and Kiran 2022 ) and indicate that people are more likely to adopt CLT when they find it convenient to use them. This implies that CLT system developers should focus on developing systems that offer user convenience.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations